Dates of publication and the organisation of Versuch einer Naturgeschichte der Krabben und Krebse by Johann Friedrich Wilhelm Herbst - Low, Martyn E. Y. (Zootaxa, 2012)
Johann Friedrich Wilhelm Herbst (b. 1743, d. 1807) published an early treatise on carcinology entitled Versuch einer Naturgeschichte der Krabben und Krebse nebst einer systematischen Beschreibung ihrer verschiedenen Arten in three Bände (= volumes, singular Band) between 1782 and 1804 (Herbst 1782–1790, 1791–1796, 1799–1804; Table 1). Each Band is comprised of four to eight Hefte (= issues or parts; singular Heft) (Table 1).